(untitled) (TAMADDUN NURI JURNALI, 2025)
This article is devoted to the analysis of animal world (paleofauna) remains found in the cultural layers of Selungur Cave, a monument of the Early Paleolithic of Central Asia. Among the paleofauna, a table of the period of life and geographical distribution of large mammals was compiled, and on this basis, scientific data on the issues of paleoecology of the Sokh oasis, nearby areas, as well as the chronology of the Selungur cave were analyzed.